The independent and interactive effects of changes in overtime and night shifts during the COVID-19 pandemic on burnout among nurses: a longitudinal study - Emanuele Maria Giusti; Giovanni Veronesi; Francesco Gianfagna; Nicola Magnavita; Francesca Campana; Rossana Borchini; Licia Iacoviello; Marco Mario Ferrario (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: This study aimed to evaluate the independent and interactive effects of changes in overtime and night shifts on burnout among nurses during the COVID-19 pandemic. METHODS: Nurses working in an Italian university hospital (N=317) completed the Maslach Burnout Inventory in September 2019 and again in December 2020. Based on hospital administrative data, changes in overtime and night shifts in the same years were categorized into three groups each. Linear regressions were used to estimate 2020 burnout differences between exposure groups, controlling for 2019 burnout levels, demographic and work-related characteristics, and to test the interaction between the two exposures. RESULTS: Nurses in the onset of high overtime group had higher emotional exhaustion [4.33, 95% confidence interval (CI) 1.74−6.92], depersonalization (2.10, 95% CI 0.49−3.71), and poor personal accomplishment (2.64, 95% CI 0.55−4.74) compared to stable low overtime nurses. Nurses in the increase in night shifts group had lower emotional exhaustion (-4.49, 95% CI -7.46− -1.52) compared to no night shift nurses. Interaction analyses revealed that this apparently paradoxical effect was limited to stable low overtime nurses only. Moreover, increases in night shifts were associated with higher depersonalization and poor personal accomplishment in nurses in the stable high overtime group. CONCLUSIONS: Increase in overtime is an independent risk factor for burnout among nurses, highlighting the need for specific regulations and actions to address it. Long-standing guidelines for the assignment of night shifts might have contributed to attenuate the impact of their increase on nurses' mental health.